PEDAGOGICAL NEED FOR THE APPEARANCE OF ORAL AND WRITTEN SPEECH TO THE DEVELOPMENT OF SPEECH COMPETENCE (Academia Science Repository, 2023)
The purpose and goals of language education, teaching speech skills, linguodidactic reasoning of components of speech competence in speech native language lessons, the cultivation of oral and written literacy, creative, scientific and creative thinking, and the improvement of students' thinking skills were all examined in this article.